2019
DOI: 10.7150/ntno.31164
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Heating Stimulated Cargo Release with Dose Control using Multifunctional MR and Thermosensitive Liposome

Abstract: Rationale: Magnetic resonance imaging (MRI) is one of the most widely used diagnostic tools in the clinic. In this setting, real-time monitoring of therapy and tumor site would give the clinicians a handle to observe therapeutic response and to quantify drug amount to optimize the treatment. In this work, we developed a liposome-based cargo (cancer drugs) delivery strategy that could simultaneously monitor the real-time alternating magnetic field-induced cargo release from the change in MRI relaxati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 89 publications
0
20
0
Order By: Relevance
“…NA is considered to be incorporated into the aqueous core of the liposomes without any precipitation because the core was observed to be clear. [18] When we evaluated diffusional transport across the synthetic membrane, no significant difference between the liposomes was observed, where the amount of the penetrated NA ranged from 20.43 to 22.89 µg cm −2 (Figure 4). Although a Franz diffusion cell is a model widely employed to compare the permeation of cosmetic products, previous reports indicated that several issues are under controversy because of the structural inconsistency to the skin tissue.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…NA is considered to be incorporated into the aqueous core of the liposomes without any precipitation because the core was observed to be clear. [18] When we evaluated diffusional transport across the synthetic membrane, no significant difference between the liposomes was observed, where the amount of the penetrated NA ranged from 20.43 to 22.89 µg cm −2 (Figure 4). Although a Franz diffusion cell is a model widely employed to compare the permeation of cosmetic products, previous reports indicated that several issues are under controversy because of the structural inconsistency to the skin tissue.…”
Section: Resultsmentioning
confidence: 96%
“…NA is considered to be incorporated into the aqueous core of the liposomes without any precipitation because the core was observed to be clear. [ 18 ]…”
Section: Resultsmentioning
confidence: 99%
“…[181] Tumor angiogenesis visualization using MRI imaging was achieved though the passive or active delivery of magnetic liposomes. [181,182] Li et al also proposed a combined approach (PDT, MRI imaging and immunotherapy), using IR dye, MRI contrast agent, and anti-EGFR antibody on liposomes for targeting, treating and imaging colorectal tumors. [183] Figure 4c summarizes the possible modifications to produce functional and stimuli responsive liposomes, in order to encapsulate and deliver drugs effectively.…”
Section: Tumor Targeted Liposomesmentioning
confidence: 99%
“…[ 181 ] Tumor angiogenesis visualization using MRI imaging was achieved though the passive or active delivery of magnetic liposomes. [ 181 , 182 ] Li et al. also proposed a combined approach (PDT, MRI imaging and immunotherapy), using IR dye, MRI contrast agent, and anti‐EGFR antibody on liposomes for targeting, treating and imaging colorectal tumors.…”
Section: Drug Delivery Systems and Droplet‐based Technologymentioning
confidence: 99%
“…[ 37 ] In other studies, Gd 3+ ‐based complexes were loaded into nanoparticles along with drug molecules to report drug release. [ 38 ] The effect of paramagnetic metal complexes is to increase the longitudinal and transverse relaxation rate of nearby water protons. Due to the fact that MRI contrast agents (especially T 1 ‐weighted MRI) depend on the access of freely diffusing water molecules, paramagnetic species inside or outside a nanocarrier provide different MRI signals for assessing drug release.…”
Section: Monitoring Drug Fatementioning
confidence: 99%